Service life of low-speed long-running stages of compressor units and possible ways of its increase - V. L. Yusha; S. S. Busarov; A. V. Nedovenchany; I. S. Busarov; R. E. Kobylskiy; D. S. Titov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents theoretical studies to increase the service life of piston seals made on the basis of fluoroplastic by changing the speed of movement of the piston and, accordingly, a more efficient cooling mode. A design with two oppositely moving pistons is proposed, which allows to increase the service life of low-speed long stroke stages